2009
DOI: 10.1007/s10765-009-0684-1
|View full text |Cite
|
Sign up to set email alerts
|

Henry’s Law Constant from Molecular Simulation: A Systematic Study of 95 Systems

Abstract: A set of molecular models from prior work for 78 pure substances is taken as a basis for systematically studying the temperature dependence of the Henry's law constant in pure solvents. All 95 binary mixtures that can be formed out of these 78 components, and for which experimental Henry's law constant data are available, are investigated by molecular simulation. The mixture models are based on the modified Lorentz-Berthelot combining rule that contains one binary interaction parameter which is adjusted to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 69 publications
0
16
1
Order By: Relevance
“…While other approaches have been used to calculate solvation free energies, alchemical free energy calculations using explicit solvent have become a mainstream approach, , in part because of their formal rigor. Alternative approaches include implicit-solvent models, , which yield Δ G hyd but do not take into consideration the solvent configuration around the solute, and Monte Carlo-based approaches using the Gibbs ensemble and expanded ensemble, though these are most commonly used for molecules that are particularly small and/or rigid.…”
Section: Introductionmentioning
confidence: 99%
“…While other approaches have been used to calculate solvation free energies, alchemical free energy calculations using explicit solvent have become a mainstream approach, , in part because of their formal rigor. Alternative approaches include implicit-solvent models, , which yield Δ G hyd but do not take into consideration the solvent configuration around the solute, and Monte Carlo-based approaches using the Gibbs ensemble and expanded ensemble, though these are most commonly used for molecules that are particularly small and/or rigid.…”
Section: Introductionmentioning
confidence: 99%
“…The force fields for Ar, N 2 , and O 2 were taken from the work of Vrabec et al These force fields were adjusted to experimental VLE data and it was shown that they are an adequate choice for numerous fluid mixtures. , For H 2 O, the widely appreciated TIP4P/2005 force field, which performs well for a large variety of thermodynamic properties, was employed.…”
Section: Methodsmentioning
confidence: 99%
“…Although the Lorentz-Berthelot combining rules are widely used to model binary mixtures, there is room for improvement. So, we have followed the procedure of Huang et al (2009) which consists in introducing an adjustable parameter, , in the Lorentz-Berthelot rule for the pair energy parameter, ,…”
Section: Appendixmentioning
confidence: 99%